Size-dependent bandgap and particle size distribution of colloidal semiconductor nanocrystals - Ferreira, D. L.; Sousa, J. C. L.; Maronesi, R. N.; Bettini, J.; Schiavon, M. A.; Teixeira, A. V. N. C.; Silva, A. G. (The Journal of Chemical Physics, 2017)
A new analytical expression for the size-dependent bandgap of colloidal semiconductor nanocrystals is proposed within the framework of the finite-depth square-well effective mass approximation in order to provide a quantitative description of the quantum confinement effect. This allows one to convert optical spectroscopic data (photoluminescence spectrum and absorbance edge) into accurate estimates for the particle size distributions of colloidal systems even if the traditional effective mass model is expected to fail, which occurs typically for very small particles belonging to the so-called strong confinement limit. By applying the reported theoretical methodologies to CdTe nanocrystals synthesized through wet chemical routes, size distributions are inferred and compared directly to those obtained from atomic force microscopy and transmission electron microscopy. This analysis can be used as a complementary tool for the characterization of nanocrystal samples of many other systems such as the II-VI and III-V semiconductor materials.
Keywords: Bandgap; Semiconductor nanocrystals